Olaratumab administered in two cases of phyllodes tumour of the breast: end of the beginning?. Issue 3 (25th June 2019) - Kyriazoglou, Anastasios; Zagouri, Flora; Dimopoulos, Meletios A
Abstract : Phyllodes tumours of the breast are rare mesenchymal tumours with differential malignant potential. Treatment of choice is radical excision with negative margins. Radiation therapy has shown controversial results in small series. Chemotherapy in the adjuvant setting still remains a matter of debate. Doxorubicin-based chemotherapy is recommended for breast sarcomas' first-line treatment. Herein we present two cases of breast phyllodes tumour treated with the recent combination of doxorubicin and olaratumab.